The Islamic Manuscripts Oskar Rescher Sold to the Leipzig University Library between 1925-1934 - Güler Doğan Averbek; Beate Wiesmüller (İslam Tetkikleri Dergisi)
Born in Stuttgart in 1883, Oskar Rescher was a prolific Orientalist of the 20th century. He lived in both Germany and Istanbul from 1909 to 1925 and settled down in Turkey in 1925. He studied many manuscripts found in private collections, libraries, and second-hand bookstores and sold thousands of manuscripts to various libraries, book antiquarians, and persons in Europe and America. Although the details have yet to be uncovered, Rescher’s manuscript sales are still talked about in certain circles; however, his manuscript trade has not been the subject of any study until ours. This article, which constitutes the fourth phase of a series of studies, draws attention to the 262 manuscripts Rescher sold to the Leipzig University Library between 1925-1934 and provides a list of these manuscripts after discussing the sales process. Thus, this study intends to direct attention to the 262 manuscripts one Orientalist scholar personally selected, evaluated, and sold. As in the example of the Berlin State Library, instead of sending the ordinary manuscripts that could be found almost anywhere, Rescher examined each manuscript and offered the ones that he found valuable in terms of content or physical characteristics. The prices he assigned were very reasonable, and there were librarians in Leipzig who think the future of these manuscripts is in danger and who attempt to collect as many manuscripts as possible. The list that has been organized with respect to the acquisition dates and numbers of each manuscript specifies the titles and author names. The list also provides the shelf numbers.